Upper and Lower $sβ(\star)$-continuous Multifunctions (European Journal of Pure and Applied Mathematics, 2023)
Our main purpose is to introduce the concepts of upper and lower $sβ(\star)$-continuous multifunctions. In particular, some characterizations of upper and lower $sβ(\star)$-continuous multifunctions are investigated. Moreover, the relationships between $sβ(\star)$-continuous multifunctions and almost $sβ(\star)$-continuous multifunctions are discussed.
Keywords: upper $sβ(\star)$-continuous multifunction; lower $sβ(\star)$-continuous multifunction